Characterization and crystallization of W200R protease - Muhd Noor, Noor Dina (2012)
Structural comparison of wild-type F1 protease and thermophilic homologues leads to hypothesis about the role of ion pairs for the thermostability of the enzymes. Higher thermostability was found to correlate with an increased number of the residues involved in ion pairs or ion pair’s networks. Therefore, W200R protease is a mutant designed to have three new additional ion pairs compared to the F1 protease. This designed mutant underwent substitution of Trp (Tryptophan) at position 200 with Arg (Arginine). Both of protease and W200R were cloned into pGEX-4T1 vector and transformed into E. coli BL21 (DE3)pLysS. For the purpose of characterization, F1 protease was purified by using Glutathione Sepharose resin and heat treatment whereby W200R was purified in three steps; Glutathione Sepharose resin, ion exchange by using Q-Sepharose Fast Flow resin and Phenyl Sepharose High Performance. The last product of purification for F1 protease and W200R was confirmed to be the mature form which is approximately 27 kDa. Characterization of W200R’s thermostability was done in comparison with F1 protease. The optimum temperature of W200R protease in the presence and absence of 2 mM CaCl2 was 75°C. Meanwhile, F1 protease exhibited a lower temperature optimum which is 70°C with the presence and absence of Ca2+. In term of thermostability in the presence of 2 mM Ca2+, the activity of W200R and F1 protease retained 100% of its activity between 50°C to 80°C and 50°C to 65°C, respectively. Ca2+ affected both enzymes by increasing and stabilizing the protease activity. The optimum pH of W200R was at pH 8 and the activity was stable in pH ranging from pH 7.0-10. The activity of W200R retained more than 100% of its activity compared to the control in the presence of miscible organic solvents log P < 2 such as pyridine, ethanol, methanol and DMSO. In comparison with the wild type, stability in the presence of immiscible organic solvents log P > 2 such as n- heptanes, hexane and benzene was exhibited. W200R protease was strongly inhibited by Phenylmethylsulfonyl fluoride (PMSF) showing that it belongs to the serine protease superfamily. W200R which was purified by using a series of purification of affinity chromatography, IEX and HIC was subjected to crystallization trial. Crystallization was set up with and without inhibitor. Crystallization screening without inhibitor on microbatch showed best crystal growth in Formulation 42 (Crystal Screen 2 kit) consists of 1.5 M Ammonium sulfate, 0.1 M Tris pH 8.5, 12% (v/v) glycerol. Optimization on crystallization temperature showed that crystallization was possible from 20°C to 40°C whereby the crystal grew as a single and bigger crystal at 20°C and fewer crystals were produced at temperature of 30°C. The number of crystals was observed to increase at 40°C. It took 30, 18 and 6 days for crystallization at 20°C, 30°C and 40°C, respectively. The crystals of W200R protease with inhibitor were obtained after 25 days of incubation at 20°C in Formulation 38 from Crystal screen 2 kit consisting of 0.1 M HEPES pH 7.5, 20% (w/v) PEG 10000. AEBSF, 5 mM was found to be the best inhibitor in contributing the crystal growth of W200R protease. However, from X-ray diffraction studies on crystals for both without and with inhibitor, it showed that the diffraction scattering intensities was low which might be due to the small size of crystals, poor crystal packing and issues regarding to crystal diffraction.